Research Trends on Parental Involvement in Inclusive Education and its Implications for Inclusive Education Programs: A Bibliometric Analysis - Kurniati, Diah; Zamroni, Edris; Utomo, Slamet; Lestari, Indah; Espejo Mirana, Ana (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This article examines research trends on parental involvement in inclusive education in reputable databases. The method used is bibliometric analysis with the Biblioshiny application and the central database analyzed from scopus.com. The keywords used were